Protein content of the male and female swimming crab Portunus pelagicus from lattakia coast - فاضل, سارة; ازدهار علي عمار; حسام الدين لايقه (Latakia University Journal -Biological Sciences Series, 2023)
This research focused on determining the protein content of samples of the swimming blue crab, Portunus pelagicus, which were collected from Lattakia beach during the summer and fall of 2020 using the method of wet digestion using sulfuric acid The protein percentages ranged between (20.43-17.95%) in females in the summer and (20.3-19.37%) in the fall, and between (12.95-19.37%) in males during the summer and (19.56-21%) in the fall. The study showed the presence of strong correlations between the percentage of protein and body weight of male and female samples of blue swimming crab P. pelagicus in the summer, where the value of the correlation coefficient was R² = 0.9058 for males and R² = 0.8358 for females. In addition to the existence of strong correlations between the percentage of protein and body weight of male and female samples of blue swimming crab P. pelagicus in the autumn season, where the value of the correlation coefficient was R² = 0.9225 for males and R² = 0.9551 for females.. Keywords: blue crab, crustacean, Syrian coast, animal benthic, protein content The current study showed that the sea crab P. pelagicus can be considered as a good source of protein and its meat consumption can be recommended as a protein-rich food item.